Standard handbook of petroleum & natural gas engineering - Lyons, William C. (Gulf Professional Pub., 2005)
"This new edition of the Standard Handbook of Petroleum and Natural Gas Engineering provides you with the best, state-of-the-art coverage for every aspect of petroleum and natural gas engineering. With thousands of illustrations and 1,600 information-packed pages, the Standard Handbook of Petroleum and Natural Gas Engineering, Second Edition is a handy and valuable references."--Jacket.